The effect of user experience and inflation technique on endotracheal tube cuff pressure using a feline airway simulator. (September 2017) - White, Donna M.; Redondo, José I.; Mair, Alastair R.; Martinez-Taboada, Fernando
Abstract: Objective: The effect of user experience and inflation technique on endotracheal tube cuff pressure using a feline airway simulator. Study design: Prospective, experimental clinical study. Methods: Participants included veterinary students at the beginning (group S1) and end (group S2) of their 2-week anaesthesia rotation and veterinary anaesthetists (group A). The feline airway simulator was designed to simulate an average size feline trachea, intubated with a 4.5 mm low-pressure, high-volume cuffed endotracheal tube, connected to a Bain breathing system with oxygen flow of 2 L minute −1 . Participants inflated the on-endotracheal tube cuff by pilot balloon palpation and by instilling the minimum occlusive volume (MOV) required for loss of airway leaks during manual ventilation. Intracuff pressures were measured by manometers obscured to participants and ideally were 20–30 cm H2 O. Student t, Fisher exact, and Chi-squared tests were used where appropriate to analyse data ( p  < 0.05). Results: Participants were 12 students and eight anaesthetists. Measured intracuff pressures for palpation and MOV, respectively, were 19 ± 12 and 29 ± 19 cm H2 O for group S1, 10 ± 5 and 20 ± 11 cm H2 O for group S2 and 13 ± 6 and 29 ± 18 cm H2 O for group A. All groups performed poorly at achieving intracuff pressures within the ideal range. There was no significant difference in intracuff pressures between techniques. Students administered lower ( p  = 0.02) intracuff pressures using palpation after their training. Conclusions and clinical relevance: When using palpation and MOV for cuff inflation operators rarely achieved optimal intracuff pressures. Experience had no effect on this skill and, as such, a cuff manometer is recommended.